PENGAPLIKASIAN KULIT PISANG KEPOK (Musa acuminate L.) UNTUK MENETRALKAN pH AIR ASAM - Herry Iswahyudi; Rismawati Rismawati (Universitas Lambung Mangkurat, 2021)
Kepok banana peel is an organic waste that has not been used properly, usually only used as animal feed. Even though banana peels contain content that can still be used, one of which is as an adsorbent material to reduce Pb in liquid waste. In this study, the kepok banana peel was used as a neutralizing agent for acid water in Jejangkit Village, Jejangkit District. The purpose of this tudy was to determine the pH value before and after the application of kepok banana peels, and to find out the best treatment from the results of the application. The treatments given to water samples taken from Jejangkit Village, Jejangkit District were 6 treatments consisting of R0 (control/without giving kepok banana peels), R1 (4 grams of banana peels/500 ml of water), R2 (5 grams of banana peels). /500 ml of water), R3 (banana peel 6 g/500 ml water), R4 (banana peel 7 g/500 ml water), and R5 (banana peel 8 g/500 ml water). Each treatment had 4 replications, so that 24 experimental units were obtained. The research parameter used to determine the effectiveness of the kepok banana peel is the pH value of the water. The results of the study obtained that the best treatment in reducing the pH value by 1 was R4 (banana peel 7 gr/500 ml of water).